A136 LIVING ON THE EDGE: EUS-DIRECTED TRANSGASTRIC ERCP (EDGE) IN PATIENTS WITH ROUX-EN-Y GASTRIC BYPASS ANATOMY. (4th March 2021) - Jain, A; Barclay, R; Donnellan, F
Abstract: Background: Roux-en-Y gastric bypass (RYGB) surgery imposes anatomic barriers to endoscopic retrograde cholangiopancreatography (ERCP). Potential options for biliary access in these patients include laparoscopic-assisted ERCP or balloon enteroscopy. However, these approaches require specialized equipment and/or operating room personnel and are associated with high rates of failure and adverse events compared to conventional ERCP. A recently described technique, EUS-directed transgastric ERCP (EDGE), is an entirely endoscopic approach which involves accessing the excluded stomach to facilitate conventional ERCP. Objectives: To describe the results of EDGE procedures performed in two centres in British Columbia. Aims: To describe the results of EDGE procedures performed in two centres in British Columbia. Methods: Data were collected from five patient cases who had undergone an EDGE procedure at Victoria General Hospital (4) or Vancouver General Hospital (1) in British Columbia from 2019 to 2020. All patients had a history of RYGB bariatric surgery. In each of the procedures, a 20 mm diameter lumen-apposing metal stent (LAMS) was deployed under EUS-guidance to allow access from the gastric remnant or proximal jejunum to the excluded stomach. Subsequently, during a separate procedure 4 to 28 days later, a duodenoscope was passed through the LAMS to perform ERCP. Following ERCP, the LAMS was removed 0 to 38 days later and replaced with a double pigtail stent to facilitate controlled closure of the gastro-jejunal or gastro-gastric fistula. Results: Of the five cases included in the case series, 4 patients underwent EDGE for treatment of choledocholithiasis and one patient underwent the procedure for gallstone pancreatitis. The technical success rate of the EDGE procedure in the five cases was 100%. Clinical success, defined by normalization of bilirubin and symptomatic relief, was observed in all of the cases. There were no adverse events related to the EDGE procedure in these five cases. Conclusions: The results of this series support EDGE as a safe and minimally invasive approach to biliary access and therapy in patients with previous RYGB surgery. Funding Agencies: None